Tantalum, Niobium, and Titanium Coating for Biocompatibility Improvement of Stainless Steel Dental Implant - M. H. Fathi (Canadian Institute of Mining, Metallurgy and Petroleum, 2007)
The aim of this work was to prepare the metallic coatings on 316L stainless steel dental implant and evaluate the corrosion characteristics and thus the biocompatibility of the uncoated and metallic coated dental implants and comparison of the effect of the type of coatings on biocompatibility. Three types of metallic coatings including Tantalum, Niobium, and Titanium coatings were made using physical vapor deposition process on 316L stainless steel dental implant. Structural characterization techniques including; X-ray Diffraction, Scanning Electron Microscopy and Energy Dispersive X-ray Analysis were utilized to investigate the microstructure and morphology of the coatings. Electrochemical potentiodynamic tests were performed in two types of physiological solutions at 37±1 °C in order to determine and compare the corrosion characteristics. All three types of metallic coatings had a positive effect on improvement of the corrosion behavior so that the coatings could increase the corrosion resistance of 316L stainless steel and this trend was independent to the type of physiological environment. Biocompatible metallic coatings could decrease the corrosion current density that is a distinct advantage for prevention of ion release. This can improve the biocompatibility of the implant and, consequently prevention of tissue damages, inflammation and irritation and obtained desirable histopathological response.